Penngaruh Citra Perusahaan Dan Pelayanan Terhadap Keputusan Penggunaan Jasa Pelanggan Pada PT. Pos Indonesia (Studi Kasus PT. Pos Indonesia KCP Bagansiapiapi) - Febri Apriansah; Uswah Hasanah (CERED Indonesia Institute, 2022)
The purpose of this study was to determine the effect of corporate image and service on the decision to use customer services at PT. Pos Indonesia KCP Bagansiapiapi. This type of research uses quantitative research. The population in this study are the customers of PT. Pos Indonesia KCP Bagansiapiapi which is located on Jl. Officer No.2 Bagansiapiapi and the samples used were 87 samples using the Slovin formula. Data collection techniques used in this study are questionnaires and documentation. The analytical model used in this study is a regression analysis model, with a partial test method with Ttest and simultaneous test with Ftest. The results of the partial T-test indicate that the company's image and service have a positive effect on the decision to use customer services partially. And the results of the F test simultaneously (simultaneously) have a positive and significant effect on the decision to use customer services. So it can be concluded that there is an influence of corporate image and service on the decision to use customer services at PT. Pos Indonesia KCP Bagansiapiapi